Mitigasi Penyebab Risiko Usahatani Kopi Arabika (Studi Kasus pada Kelompok Tani Hutan Giri Senang, Kampung Legok Nyenang, Kecamatan Cilengkrang, Kabupaten Bandung) - Omar, Natasha Margaretha Wiryawan; Djuwendah, Endah; Trimo, Lucyana; Mukti, Gema Wibawa (Universitas Galuh, 2024)
The Giri Senang Forest Farmer Group (KTH) has experienced a significant decline in arabica coffee production over the past few years. This indicates the existence of risks that need to be addressed immediately. The research was conducted with the aim of identifying the causes of risks in arabica coffee farming, understanding the mitigation actions that have been taken by KTH Giri Senang, and proposing mitigation actions that can be implemented to overcome these problems. The research was carried out using descriptive qualitative analysis with a case study research technique. The causes of risk were identified using a Fishbone Diagram and analyzed with the Failure Mode and Effect Analysis (FMEA) method. Based on the results of the research, there are 7 priority risk causes out of 26 total causes: unfavorable weather, leaf rust disease, insufficient or excessive rainfall, leaf spot disease, coffee berry borer pests, weather changes due to the La Nina-El Nino phenomenon, and lack of pruning. Mitigation actions that have been taken include making a holding pond, using pesticides, traps, pest control agents, harvesting spoils, and sanitation to eradicate pests and diseases, as well as forming a Pest Control Team. Proposed mitigation actions that can be implemented include organizing agricultural insurance, subsidizing insurance premiums, making holes or roraks, switching to organic farming, using spare harvest bags, collaborating with educational or research institutions, holding discussion forums for farmers, and creating video tutorials and educational content as alternative extension activities.